Equitable and inclusive school education : ideation to implementation - Kaushik, Bharti (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This book highlights the strategies and approaches to the practice of equitable and inclusive school education, elaborating the role of various stakeholders such as teachers, special educators, parents, peers, teacher educators, educational administrators, and Ed-tech firms. The aim of this book is to create understanding about equitable and inclusive school education which is not restricted to children with disabilities but also includes children with different learning needs as well as those from the socially and economically disadvantaged sections of society. The focus is on presenting practical strategies that are grounded in theory and supported with research. The significance of screening at the classroom level, development of need based accessible learning teaching materials, customizing the pedagogy practices for inclusive classrooms, need based examination accommodations, leveraging the potential of ICT to elicit participation of all and collaborative efforts towards realizing the optimum potential of each learner are few basic ideas illustrated in the book with examples. The volume also discusses recent national and international policies for equitable and inclusive education, recommending courses of action for effective implementation of the existing provisions by teachers and educators. The book will be useful to students, researchers, teacher-educators, special educators, special education teacher educators, pre-service teachers, and parents. It will also be an invaluable companion to in-service teachers, policy makers and educational administrators, curriculum developers, and NGOs working in the field of inclusive education"--
Decoding equitable and inclusive education / Bharti Kauhsik -- Equitable and inclusive education for children with disabilities (CwD) / -- Abhishek Kumar Srivastava -- Diverse needs of learners' from SEDG background / Bharti Kaushik -- Identification and assessment of special needs for education / Bharti Kaushik -- Equitable and inclusive classrooms and schools / Bharti Kaushik -- Policy perspectives, provisions and institutions / Bharti Kaushik -- Inclusive pedagogical practices / Bharti Kaushik -- Support services / Hillol Mukherjee -- Assistive technology and CCE / Manoj Kumar and Bharti Kaushik -- Support services and role of stakeholders towards equitable and inclusive education / Bharti Kaushik.
Keywords: Educational equalization; Inclusive education; Children with disabilities -- Education; Classroom environment; EDUCATION / Educational Policy & Reform / General